Negative-electrode-free sodium battery based on hexagonal boron nitride modified electrolyte and current collector

By using hexagonal boron nitride organic electrolyte and current collector in an anode-free sodium battery, combined with a sodium vanadium phosphate positive electrode sheet and a Celgard separator, the problem of poor circulation and rate performance of an anode-free sodium battery under large current is solved, and the problem of poor circulation and magnification performance of a negative-free sodium battery under large current is achieved. Higher stability and battery capacity.

CN119230941APending Publication Date: 2024-12-31NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411570427.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

There is a gap in the circulation and rate performance of the negative-node sodium batteries, especially when operating under high currents, they face the problems of stability and battery capacity loss.

Method used

The organic electrolyte with hexagonal boron nitride and current collector are used, combined with sodium vanadium phosphate positive electrode sheet and Celgard separator, and the cycling and rate performance of the battery is improved through the design of the nanodispersed phase.

Benefits of technology

The negative-node sodium battery is achieved to work stably under large currents, which improves cycle stability and charge-discharge specific capacity, reduces the probability of dendrite formation and the desolvation energy barrier of the electrolyte, and enhances the dynamic process of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230941A_ABST
    Figure CN119230941A_ABST
Patent Text Reader

Abstract

The invention discloses a negative-electrode-free sodium battery based on hexagonal boron nitride modified electrolyte and a current collector, and belongs to the technical field of energy storage materials, the electrolyte comprises hexagonal boron nitride h-BN, sodium hexafluorophosphate NaPF6 and diethylene glycol dimethyl ether G2; the concentration of the sodium hexafluorophosphate is 1 mol / L, and the concentration of the hexagonal boron nitride is 150 g / L. And the current collector comprises a conductive agent SuperP, nano dispersed phase hexagonal boron nitride h-BN and a binder polyvinylidene fluoride (PVDF) in a mass ratio of 5: 5: 1, and the blade coating thickness is 20 [mu] m. The negative-electrode-free sodium battery comprises a battery shell, a positive pole piece, an electrolyte, a current collector and a diaphragm located between the positive pole piece and a negative pole piece are arranged in the battery shell, the electrolyte is an organic electrolyte with hexagonal boron nitride, and the current collector is a current collector with a nano dispersed phase. According to the synergistic effect of the current collector and the electrolyte, the problem that the negative-electrode-free sodium battery cannot work under large current is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of energy storage materials, and in particular relates to an organic electrolyte with a nano-dispersed phase, a current collector and a negative electrode-free sodium battery. Background Art

[0002] The adjustment of energy structure is an important issue for the development of energy industry in the 21st century. The efficient storage of renewable energy has attracted more and more attention. The pursuit of low-pollution, low-cost, high-performance reversible secondary batteries has become an important trend. In the field of electrochemical energy storage, sodium-ion batteries and lithium-ion batteries have similar working principles, and sodium has natural resource and cost advantages such as abundant reserves, wide distribution, and low price. Therefore, sodium-ion batteries are considered to be very competitive energy storage batteries. However, with the continuous exploration of aerospace, deep sea and other fields, batteries are more required to have excellent charge and discharge performance under large currents, especially to have higher energy density.

[0003] Although the negative electrode-free sodium battery is an ideal high energy density system, the irreversible loss of sodium ions caused by the generation of "dead sodium" and the side reaction between the electrolyte and metallic sodium during the cycle process will directly reflect the loss of battery capacity. Therefore, compared with sodium ion batteries and sodium metal batteries, negative electrode-free sodium batteries face more severe challenges in cycle life, especially when operating at high currents.

[0004] Therefore, there is an urgent need to develop a negative electrode-free sodium battery that can operate stably under large current to further solve the above problems. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an organic electrolyte, a current collector and a negative electrode-free sodium battery with hexagonal boron nitride, to construct a negative electrode-free sodium battery with excellent rate and cycle performance, and to solve the problem of poor cycle and rate performance of current negative electrode-free sodium batteries.

[0006] An organic electrolyte with hexagonal boron nitride comprises hexagonal boron nitride h-BN, sodium hexafluorophosphate NaPF6 and diethylene glycol dimethyl ether G2; the concentration of the sodium hexafluorophosphate is 1 mol / L, and the concentration of the hexagonal boron nitride is 150 g / L.

[0007] A current collector with hexagonal boron nitride comprises a conductive agent SuperP, a nano-dispersed phase hexagonal boron nitride h-BN and a binder polyvinylidene fluoride PVDF, the mass ratio of which is 5:5:1, and the coating thickness is 20um.

[0008] A negative electrode-free sodium battery comprises a battery shell, wherein a positive electrode sheet, an electrolyte, a current collector, and a diaphragm located between the positive electrode sheet and the negative electrode sheet are arranged in the battery shell, wherein the electrode liquid is an organic electrolyte with a nano-dispersed phase, and the current collector is a current collector with a nano-dispersed phase.

[0009] The diaphragm adopts a double-layer Celgard diaphragm.

[0010] The active material used in the positive electrode plate is sodium vanadium phosphate, the conductive agent is acetylene black, the binder is polytetrafluoroethylene, and the current collector of the positive electrode plate is aluminum.

[0011] Through the above design scheme, the present invention can bring the following beneficial effects: an organic electrolyte with a nano-dispersed phase, a current collector and a negative electrode-free sodium battery, which are simple to prepare and have cheap raw materials; further, considering that Lewis acidic particles can capture anions to form a space charge layer characterized by cation aggregation, thereby obtaining a higher Na + transfer number, and in some cases even a higher total conductivity can be obtained. Furthermore, the stronger the acidity of the compound, the stronger its tendency to adsorb anions. This not only means reduced concentration polarization and reduced probability of dendrite formation, but also reduces the desolvation energy barrier of the electrolyte compared to traditional electrolytes, accelerating the kinetic process inside the battery. When it is used as a current collector, a double layer dominated by anions is constructed on the surface, thereby forming an inorganic SEI rich in inorganic components and effectively inhibiting dendrite growth. The synergistic effect of the current collector and the electrolyte solves the problem that negative electrode-free sodium batteries cannot work at high currents. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] The present invention is further described below with reference to the accompanying drawings and specific embodiments:

[0013] Figure 1 This is a comparison chart of battery performance when the organic electrolyte prepared in Example 1 of the present invention and the electrolyte prepared in Comparative Example 1 were applied at 25°C.

[0014] Figure 2 The diagram shows the action mechanism of the current collector prepared in Example 2 of the present invention and the sodium metal deposition and stripping efficiency when it is applied in REE electrolyte.

[0015] Figure 3 This is a comparison chart of battery performance at 25°C of the NVP||Sup@BN negative electrode-free sodium battery prepared in Example 3 of the present invention and the electrolyte of Comparative Example 1.

[0016] Figure 4 This is a graph showing the cycle performance and charge-discharge curve of the NVP||Sup@BN negative electrode-free sodium battery prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0017] The present invention will be described in detail below in conjunction with the accompanying drawings and embodiments. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] The preparation method is specifically described below in conjunction with the accompanying drawings and examples. However, it should be understood that the examples are only used to illustrate the present invention and do not limit the scope of protection of the present invention in any way.

[0019] Example 1

[0020] This example provides a NVP||Al negative electrode-free and Na||Al half-cell, and the specific steps are as follows:

[0021] Step (1), preparation of electrolyte: prepare electrolyte in a glove box filled with argon, weigh 100 mg, 150 mg, and 200 mg h-BN respectively, disperse them in 1M NaPF6 in G2 (denoted as REE) electrolyte, and stir evenly to obtain different h-BN electrolytes, denoted as 100BN, 150BN, and 200BN respectively;

[0022] Step (2), preparation of the positive electrode sheet: NVP, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 80:10:10 and fully ground, and N-methylpyrrolidone (NMP) is added to form a slurry, which is coated on the surface of the aluminum foil, and then placed in a vacuum drying oven at 120°C for 12 hours. Finally, the aluminum foil coated with the active material is cut into 14 mm discs to form a positive electrode sheet, and the loading amount of the active material in the positive electrode sheet is about 12 mg;

[0023] Step (3), assembly of NVP||Al anode-free battery: assembling CR2032 button cells in a glove box filled with argon, using NVP as the positive electrode, Al as the negative electrode, two layers of Celgard separators and the electrolyte in this embodiment to assemble into an anode-free sodium battery;

[0024] Step (4), assembly of Na||Al half-cell: assembling CR2032 button cells in a glove box filled with argon, using Na metal as the positive electrode, Al as the negative electrode, two layers of Celgard separators and the electrolyte in this embodiment to assemble into a Na||Al half-cell;

[0025] Step (5), electrochemical performance test of the battery: The battery in steps (3) and (4) of this embodiment was placed in a constant temperature and humidity chamber at 25°C and subjected to cross-current charge and discharge tests (1C = 117 mAh g -1, voltage range 2,6-3.8V) and sodium metal deposition stripping test (test current 1mA cm -2 , deposition capacity is 1 mA cm -2 , cut-off voltage is 1V), test results are shown in Figure 1 and Figure 2 .

[0026] Comparative Example 1

[0027] This example provides a NVP||Al negative electrode-free battery, and the specific steps are as follows:

[0028] Step (1), preparation of electrolyte: weigh 1 M NaPF6, dissolve it in 1 M G2, and name it REE;

[0029] Step (2), preparation of the positive electrode sheet: NVP, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 80:10:10 and fully ground, and N-methylpyrrolidone (NMP) is added to form a slurry, which is coated on the surface of the aluminum foil, and then placed in a vacuum drying oven at 120°C for 12 hours. Finally, the aluminum foil coated with the active material is cut into 14 mm discs to form a positive electrode sheet, and the loading amount of the active material in the positive electrode sheet is about 12 mg;

[0030] Step (3), assembly of NVP||Al negative electrode-free battery: assemble a CR2032 button battery in a glove box filled with argon gas, using NVP as the negative electrode, Al as the negative electrode, two layers of Celgard as the separator and the electrolyte in step (1) of this embodiment to assemble a negative electrode-free sodium battery;

[0031] Step (4), electrochemical performance test of sodium ion battery: The sodium ion battery in step (3) of this embodiment is placed in a constant temperature and humidity chamber at 25°C and a constant current charge and discharge test (1C = 117 mAh g -1 , voltage range is 2.6-3.8V), test results are shown in Figure 1 , where a) and b) NVP||Al anode-free battery cycling performance; c) Na||Al battery coulombic efficiency; d) REE electrolyte nucleation overpotential for Al.

[0032] Figure 1 : Cycling at 0.5C, the cycling stability of 100BN electrolyte is greatly improved compared with REE. After 200 cycles, the capacity is 63mAh g -1 , while REE is only 18 mAh g -1 ( Figure 1a). Subsequently, the concentration of h-BN was increased. It was found that with the increase of h-BN addition, the battery decayed faster in the early stage. The battery with 200BN electrolyte decayed from 92 mAh g in 10 cycles. -1 Decay to 76 mAh g -1 , but when the battery is stable, it has strong stability ( Figure 1 b). Assemble Na||Al batteries to investigate the attenuation reasons. It was found that the deposition and stripping efficiency of high-concentration REE (150BN) electrolyte was low, and it still could not reach 99% after 5 cycles. The nucleation overpotential was greater than 30mV, which easily caused dendrite growth and eventually formed dead sodium ( Figure 1 c and 1d).

[0033] Example 2

[0034] This example provides a half-cell with a metallic sodium current collector, and the specific steps are as follows:

[0035] Step (1), preparation of current collector: h-BN, conductive agent and binder were ground in a ratio of 5:5:1, then NMP was added to make slurry, and then coated on aluminum foil with a thickness of 20um, and then placed in a vacuum drying oven at 120°C for 12 hours, and finally the aluminum foil was cut into 19mm discs to form a modified current collector. The conductive agents selected were carbon nanotubes (CNT), graphite (Gr) and SuperP;

[0036] Step (2), assembly of half-cell: assembling CR2032 button cells in a glove box filled with argon, using metallic sodium as the positive electrode, two layers of Celgard as the separator and the three current collectors in this embodiment to assemble the half-cell;

[0037] Step (3), electrochemical performance test: The half-cell in step (3) of this embodiment was placed in a constant temperature and humidity chamber at 25°C and subjected to a sodium metal deposition stripping test on a blue electric test system (test current was 1 mA cm -2 , deposition capacity is 1 mA cm -2 , cut-off voltage is 1V), test results are shown in Figure 2 , including: a) schematic diagram of the action mechanism; b) statistics of nucleation overpotential; c) coulombic efficiency of Na||Sup@BN battery.

[0038] Figure 2 :h-BN is coated on the current collector, which will adsorb a large number of anions on the surface of the current collector and induce the sodium ions to approach through electrostatic induction. Finally, the electrolyte in the surface area of ​​the current collector is equivalent to a local high-concentration electrolyte, which helps to form anion-derived inorganic SEI and inhibit the growth of sodium dendrites ( Figure 2a). Based on the nucleation overpotential and deposition stripping efficiency, the conductive agent is selected as Super P, and the constructed current collector is denoted as Sup@BN. The nucleation potential of the Na||Sup@BN battery is only 17mV, and the coulombic efficiency reaches 99.8% ( Figure 2 b and 2c).

[0039] Example 3

[0040] This example provides a NVP||Sup@BN negative electrode-free sodium battery. The specific steps are as follows:

[0041] Step (1), preparation of electrolyte: prepare electrolyte in a glove box filled with argon, weigh 100 mg, 150 mg, and 200 mg h-BN respectively, disperse them in 1M NaPF6 in G2 (denoted as REE) electrolyte, and stir evenly to obtain different h-BN electrolytes, denoted as 100BN, 150BN, and 200BN respectively;

[0042] Step (2), preparation of the positive electrode sheet: NVP, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 80:10:10 and fully ground, and N-methylpyrrolidone (NMP) is added to form a slurry, which is coated on the surface of the aluminum foil, and then placed in a vacuum drying oven at 120°C for 12 hours. Finally, the aluminum foil coated with the active material is cut into 14 mm discs to form a positive electrode sheet, and the loading amount of the active material in the positive electrode sheet is about 12 mg;

[0043] Step (3), preparation of Sup@BN current collector: h-BN, SuperP and binder were ground in a ratio of 5:5:1, then NMP was added to make a slurry, and the slurry was applied on an aluminum foil with a thickness of 20 μm, and then placed in a vacuum drying oven at 120°C for 12 h, and finally the aluminum foil was cut into 19 mm discs to form a modified current collector;

[0044] Step (4), assembly of NVP||Sup@BN anode-free sodium battery: assembling CR2032 button cells in a glove box filled with argon, using NVP as the positive electrode, Sup@BN as the negative electrode, two layers of Celgard separator and the electrolyte in this embodiment to assemble into an anode-free sodium battery;

[0045] Step (5), electrochemical performance test of the battery: The battery in step (4) of this embodiment was placed in a constant temperature and humidity chamber at 25°C and subjected to rate and constant current charge and discharge tests (1C = 117 mAh g -1 , voltage range is 2.6-3.8V), test results are shown in Figure 3, among which, a) 25℃ rate performance; b) and c) charge-discharge curves of REE-based electrolyte and SCE electrolyte; d)-f) rate performance and charge-discharge curves of different contents of h-BN; Figure 4 , where a) cycle performance; b) charge and discharge curves.

[0046] Figure 3 - Figure 5: 82 mAh g at 5C rate in a 150BN-based battery -1 The ultra-high specific capacity of REE electrolyte is short-circuited at 3C. The corresponding capacities of 100BN and 200BN batteries at 5C are 58mAh g -1 and 73mAh g -1 The specific capacity ( Figure 3 ). The NVP||Sup@BN battery assembled with 150BN electrolyte was tested for long cycle performance. The test current density was 5C. The results showed that the battery with 150BN electrolyte needs 300 cycles to decay to 80%, and 870 cycles to decay to 60% ( Figure 4 ).

[0047] In summary, the present invention improves the electrochemical performance of the negative electrode-free sodium battery by configuring an organic electrolyte and a current collector with a nano-dispersed phase, so that the battery has a stable charge and discharge specific capacity and a high rate performance. Therefore, the electrolyte and current collector provided by the present invention have potential application value.

[0048] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to the embodiments will be apparent to one skilled in the art, and the general principles defined in the present invention may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An organic electrolyte having hexagonal boron nitride, characterized in that: It includes hexagonal boron nitride h-BN, sodium hexafluorophosphate NaPF6 and diethylene glycol dimethyl ether G2; the concentration of the sodium hexafluorophosphate is 1 mol / L, and the concentration of the hexagonal boron nitride is 150 g / L.

2. A current collector having hexagonal boron nitride, characterized in that: It includes a conductive agent SuperP, a nano-dispersed phase hexagonal boron nitride h-BN and a binder polyvinylidene fluoride PVDF, with a mass ratio of 5:5:1 and a coating thickness of 20um.

3. A negative electrode-free sodium battery, characterized in that: The invention comprises a battery shell, in which a positive electrode sheet, an electrolyte, a current collector and a diaphragm located between the positive electrode sheet and the negative electrode sheet are arranged. The electrode liquid is an organic electrolyte containing hexagonal boron nitride, and the current collector is a current collector containing hexagonal boron nitride.

4. A negative electrode-free sodium battery according to claim 3, characterized in that: The diaphragm adopts a double-layer Celgard diaphragm.

5. A negative electrode-free sodium battery according to claim 3, characterized in that: The active material used in the positive electrode plate is sodium vanadium phosphate, the conductive agent is acetylene black, the binder is polytetrafluoroethylene, and the current collector of the positive electrode plate is aluminum.

Citation Information

Cited By

  • Battery monomer and manufacturing method thereof, battery device, power utilization device and energy storage device

    CN122000482A

  • Modified boron nitride nanosheet, preparation method thereof, current collector and sodium battery without negative electrode

    CN122968304A